Theory, practice and upgrading of pairwise assistance: A literature review and inspiration - Wang, Jian-ying; Wang, Yu-ying; Chen, Kevin Z. (China Academic Journals Electronic Publishing House Co., 2023)
As a regional policy with distinct Chinese characteristics, the series of pairwise assistance policies play a key role in China’s poverty reduction, emergency management, regional governance, and other fields. Pairwise assistance policies are effective measures of narrowing regional gaps, promoting regional coordinated development, and optimizing the national governance system. Pairwise assistance policies are also very important to achieve common prosperity and boost Chinese-style modernization. Only a few studies focused on the topic of pairwise assistance, and there was no good summary review from the perspectives of the theoretical basis and practical experience of pairwise assistance.This paper summarizes the theoretical basis of pairwise assistance from the perspectives of horizontal transfer payment and input and transformation of production factors. The policy evolution of pairwise assistance in China is divided into four stages: the germination stage, development stage, improvement stage, and upgrading stage. Further, from economic and intellectual perspectives, the policy tools of pairwise assistance are analyzed. The practical effect of pairwise assistance is summarized from five aspects, which are economic driving, regional development coordination, poverty alleviation, governance, and public services. It is found that in the new era, pairwise assistance needs to refine the role of government, improve the enthusiasm of participants, and improve the efficiency of project implementation. We point out that future research on pairwise assistance should focus on the study of practical mechanisms, quantitative assessment of policy effect, and the scaling up of pairwise assistance models. This can further provide support to enhance the system building and improve the effectiveness of pairwise assistance policies.This paper contributes to the existing literature in four aspects: firstly, we attempted to sort out the economic theoretical basis for the implementation of pairwise assistance; secondly, we analyzed the possible paths and policy effectiveness of pairwise assistance to promote the socio-economic development of recipient areas; thirdly, we attempted to put forward targeted enlightenment for the optimization and upgrading of pairwise assistance based on the problems existing in the implementation of the policies, so as to meet the new requirements for the pairwise assistance in the new era; fourthly, we tried to summarize the possible gaps in existing related research and future research directions.With the gradual advancement of the process of Chinese-style modernization, the application field of pairwise assistance is more extensive. It is of great significance for us to summarize the practical experience of pairwise assistance in the past 40 years, to upgrade the pairwise assistance and conform to the development requirements of the new era. This paper can provide a useful reference for optimizing pairwise assistance, promoting economic development in underdeveloped areas, providing an experience for promoting coordinated regional development and upgrading the national governance system and governance capacity.